INSTRUMENTS OF THE STATE POLICY OF IMPROVEMENT OF THE INSTITUTIONAL ENVIRONMENT OF DEVELOPMENT OF SMALL BUSINESS IN UKRAINE AS A FACTOR OF REGULATION OF MIGRATORY ACTIVITY OF THE POPULATION - BARNA, MARTA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article points out the key problematic aspects of the functioning and development of the national economy of Ukraine in terms of intensification of migration processes, including external, labor. These are the loss of intellectual and human capital, the formation of a labor market shortage, the degradation of territories, the reduction of revenues to central and local budgets, the aggravation of social problems and the growing burden on budgets, and so on. The urgency of formation and implementation of an effective state policy focused on restraining the volume of external and using the potential of internal migration in Ukraine is substantiated. It is proved that one of the most effective tools of state regulation of the economy in this context is to ensure self-employment by starting and successfully running a private business. At the same time, this requires a significant improvement in the business environment in Ukraine. It is shown that one of the priority components of a quality business environment is the infrastructure to support entrepreneurship. Current proposals to improve the institutional environment to support small business development in Ukraine are substantiated. The priorities of the state policy of improving the associative and public infrastructure of entrepreneurial activity as an important area of ​​support for small and medium enterprises and thus curbing migration processes in Ukraine include: 1) development and increase of competencies of associative business organizations; 2) ensuring cooperation between civil society organizations and associative business structures; 3) strengthening the interaction of government, associative business structures and civil society organizations in the field of transaction cost management. The scientific novelty of the study lies in the substantiation of a new institutional form of stimulating the development of small business in the country, as an institutional tripartite partnership of government officials and collective organizations of business and society. The practical significance of the research results is to use reasonable proposals in order to improve the existing infrastructure in Ukraine to support private business.